Study of the Effect in the Output Membership Function When Tuning a Fuzzy Logic Controller - Mohd Aras, Mohd Shahrieel; Abdul Azis, Fadilah; Fara Ashikin , Ali; Syed Mohamad Shazali, Syed Abdul Hamid (2012)
This paper describes a study of tuning process for fuzzy logic controller (FLC) design. In fuzzy logic controller design, there is no systematic procedure to tune fuzzy logic controller to follow a desired set point. The tuning process of Fuzzy Logic Controllers (FLCs) using trial-and-error approach is commonly done until satisfactory results are obtained. This is usually a tedious and time-consuming task but it has been widely employed and has been used in many successful industrial applications. The performance of the system can be analyzed. If the results are not as desired, changes are made either to the number of the fuzzy partitions or the mapping of the membership function and then the system can be tested again. This paper demonstrates a faster tuning process by adjusting the mapping of the membership function to get desired output. Through identifying and analyzing what will be done on adjusting mapping of membership functions by utilizing knowledge from the experts, it will be demonstrated in this paper that the tuning process of FLCs can be easily simplified.